Study of Tajweed and Waqf Marks in the Qur'an Bone Mushaf - El Karimah, Mia Fitriah (Sinergi International Journal of Islamic Studies, 2023)
The purpose of this paper is to describe the characteristics of the Bone manuscript from the aspect of punctuation, both tajweed and waqaf. Because this manuscript is so complex, all aspects touch on every part of this manuscript, the aspects that will be discussed in this manuscript are aspects of tajwid and waqf signs. Reading the Qur'an with recitation is a non-negotiable necessity, so it is important to pay attention to the laws of nūn mati, mim mati, ikhfa or iqlab, as well as about the law of reading mad and others. This is the reason why the ancient Qur'anic copiers included the tajweed signs they thought were necessary. In this ancient mushaf, for example, it is clear about the efforts made by the writers to give certain signs to the tajwid readings and so do the waqf signs. For tajwid markings on Bone mushafs, use the letter غ for gunnah, the letter خ for ikhfa' and the letter ظ for idzhar reading, for mad obligatory muttasisil readings it is marked with a set of three lines with a red line above. While reading mad jaiz munfasil is marked with a red line. Meanwhile, the waqf sign used in this manuscript is ط for mutlaq waqf, the letter ك is for waqaf kafi', and the letter ت is for tamm waqf.